Under-forest composite planting medicinal material seedling raising device and use method thereof - LI JUNNAN; LIANG LINBO; LI HONGXU; HOU MIN; MOU XIANGHU; XIONG XINWU; FAN HAIXIA; FENG YONGXING; SU LIANBO; YANG WENJUN; LI RONGBO; ZHAO QIANCHI; et al. (2024)
The under-forest composite planting medicinal material seedling raising device comprises a seedling raising frame, supports are fixedly connected to the four corners of the top face of the seedling raising frame, triangular blocks are fixedly connected to the top faces of the supports, mounting parts are fixedly connected to the four corners of the bottom face of the seedling raising frame, and a plurality of seedling raising parts are arranged on the top face of the seedling raising frame in a uniform arrangement structure; a plurality of seedling raising grooves are formed in the top surface of the seedling raising plate, seedling raising containers are inserted into the seedling raising grooves, a windproof cover sleeves the outer wall of the seedling raising frame, a protection part is arranged above the seedling raising frame, a metal protection net is arranged on the protection part, triangular grooves are formed in the four corners of the metal protection net, and an irrigation part is arranged below t